DETECÇÃO DE BEAUVERICINA EM FRUTOS DE ABACAXI INFECTADOS POR Fusarium guttiforme POR HPLC-DAD E MALDI-FT-ICR MS - Carolinne S. Fávero; Nayara A. dos Santos; Wanderson Romão; Raissa D. Moura; Christiane F. de Castro Porto; José Aires Ventura (Química Nova, 2024)
Pineapple, important in Brazilian fruit growing and highly consumed worldwide, can be affected by fusariosis, a disease caused by Fusarium guttiforme, which compromises the quality of the fruit and produces a mycotoxin called beauvericin (BEA), which is harmful to the health of consumers. The importance of detecting BEA and establishing maximum permitted limits is urgent, as there are few studies on this mycotoxin and there is still no regulation in world legislation. In this work, methodologies were used to detect BEA using HPLC-DAD and MALDI-FT-ICR MS. The results of HPLC-DAD allowed the detection of BEA in the tissues of the samples with F. guttiforme, evidenced by chromatographic peaks in the retention time, 6.1 min, similar to the standard, however, in the samples of visibly healthy tissue the mycotoxin was not detected. With MALDI-FT-ICR MS, BEA was detected with mass errors of less than 1 ppm in all samples (tissues infected with F. guttiforme and in healthy tissues), showing that, in addition to the greater sensitivity of the method, there is the possibility of mycotoxin diffusion in the healthy tissues of fruits inoculated with F. guttiforme, when these tissues are also contaminated.